Necrotizing Pseudomonas aeruginosa Community-Acquired Pneumonia: A Case Report and Review of the Literature - Satish Maharaj; Carmen Isache; Karan Seegobin; Simone Chang; Grant Nelson (Case Reports in Infectious Diseases)
Lung cavities are not typically associated with community-acquired pneumonia (CAP). CAP due to P. aeruginosa is rare and even less commonly causes necrotizing pneumonia. We report a case of P. aeruginosa CAP that progressed to necrotizing pneumonia and was eventually fatal. Procalcitonin (PCT) has been well investigated in guiding antibiotic therapy (especially CAP) in adults. In this case, PCT at presentation and sequentially was negative. We discuss this caveat and present hypotheses as to the sensitivity and specificity of PCT and C-reactive protein (CRP) in these patients. To better characterize P. aeruginosa CAP, we undertook a review of cases indexed in PubMed from 2001 to 2016 (n=9). The data reveal that risk factors for P. aeruginosa CAP include smoking, alcohol use, obstructive lung disease, sinusitis, and hot tub use. The route of infection for P. aeruginosa CAP remains unknown. One of the most interesting findings on reviewing cases was that P. aeruginosa CAP involves the right upper lobe in the vast majority. We suggest that when physicians in the community see patients with distinctly upper lobe necrotizing or cavitary pneumonia, they should consider P. aeruginosa in their differential diagnosis. Further studies are needed to clarify route of infection, role of PCT and CRP, and optimal therapy including drug and duration.